2019
DOI: 10.1111/cgf.13693
|View full text |Cite
|
Sign up to set email alerts
|

Robust Extraction and Simplification of 2D Symmetric Tensor Field Topology

Abstract: In this work, we propose a controlled simplification strategy for degenerated points in symmetric 2D tensor fields that is based on the topological notion of robustness. Robustness measures the structural stability of the degenerate points with respect to variation in the underlying field. We consider an entire pipeline for generating a hierarchical set of degenerate points based on their robustness values. Such a pipeline includes the following steps: the stable extraction and classification of degenerate poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…By extending this concept to two-dimensional symmetric second-order tensor fields, a basis for hierarchical-based tensor field topology simplification was created. Jankowai et al [JWH19] extended this work by presenting a computational pipeline for generating a hierarchical set of degenerate points, indicating their likelihood to cancel at field perturbation.…”
Section: Topology Simplificationmentioning
confidence: 91%
“…By extending this concept to two-dimensional symmetric second-order tensor fields, a basis for hierarchical-based tensor field topology simplification was created. Jankowai et al [JWH19] extended this work by presenting a computational pipeline for generating a hierarchical set of degenerate points, indicating their likelihood to cancel at field perturbation.…”
Section: Topology Simplificationmentioning
confidence: 91%
“…Lately, Wang et al [WBR*17] further extended the classic definition of robustness to a Galilean invariant robustness framework that quantifies the stability of critical points across different frames of reference. The notion of robustness was further extended to study the stability of degenerate points in tensor fields [WH17,JWH19]. The concept of robustness, first introduced by Edelsbrunner et al [EMP11b,EMP11a], is closely related to the notion of persistence [ELZ02] -a common tool used to quantify feature importance.…”
Section: Related Workmentioning
confidence: 99%
“…. It has been shown that this value is also related to the stability of degenerate points in tensor field topology [11] and is the measure we are mostly interested in. In the following, we will however consider the squared value of α(T ), which has the same topological characteristics but simplifies the computations a lot.…”
Section: Second Order Symmetric Tensors and Anisotropymentioning
confidence: 99%
“…Further, it is frequently used in mechanical engineering applications to analyze the failure of materials. The join tree, a subset of the contour tree, of this anisotropy can be used for a topology-preserving simplification of 2d tensor fields [11].…”
Section: Introductionmentioning
confidence: 99%